Quality of comprehensive assessment among severely ill TB patients referred after triaging in southern India - H. D. Shewade; A. Frederick; S. Kiran Pradeep; T. Daniel Rajasekar; G. Kiruthika; T. Bhatnagar; K. V. Suma; P. Ravichandran; K. Gayathri; R. Vijayaprabha; D. P. Pathinathan; D. Chidambaram; et al. (The Union, 2024)
To reduce TB deaths, Tamil Nadu, a southern Indian state, implemented the first state-wide differentiated TB care strategy starting April 2022. Triage-positive severely ill patients are prioritised for comprehensive assessment and inpatient care. Routine program data during October-December 2022 revealed that documentation of total score after comprehensive assessment was available in only 39%, possibly indicating poor quality of comprehensive assessment. We confirmed this using operational research. The case record form to record comprehensive assessment was used only in 26% and among these, the completeness and correctness in filling out the form were sub-optimal. There is a clear need to enhance the quality of comprehensive assessments.